The Effect of SKJ 2017 Exercise and Low Impact Aerobic Exercise on Balance and Vo2Max - Annas Pra Ghoniyyu Qolbi; Oce Wiriawan; Hari Setijono (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The purpose of this study was to analyze the effect before and after the 2017 SKJ exercise to improve balance, to analyze the effect before and after the 2017 SKJ exercise to increase VO2Max, to analyze the effect before and after aerobic Gymnastics exercise Low Impact to improve balance. after the aerobics exercise Low Impact to increase VO2Max, analyze the differences between SKJ 2017 and aerobic exercises Low Impact on balance, and analyze the differences in SKJ 2017 and aerobic exercises Low Impact on VO2Max. This study uses a method (quasi-experimental research quasi-experimental research). The quasi-experimental research method is used as experimental research. This research method is carried out by conducting experiments (trials) with the type of subject installation design through a pre-test and a post-test with the control group. The matching only pretest-posttest control group design type of design is a study that matches subjects in the control group and the experimental group with data analysis using ANOVA. The data collection process was taken by testing the balance using the test balance beam and VO2Max using the MFT. Then the data were analyzed using the SPSS 23 series. The target of this study was members of the UNESA Gymnastics UKM with 30 members, divided into 3 groups with 10 people in each group, this research was conducted for 6 weeks. Results Pairedsamplest-test, strength, and paired sample t-test limb muscle power that the level of significance of each variable obtained sig 0.000 <0.05 so that there is a significant or significant difference between pretest and posttest of the dependent variable balance and VO2Max.The results of the ANOVA test revealed that the significance value was less than 0.05 (0.03 <0.05), the conclusion was that the average balance results of the three groups were significantly DIFFERENT. Then it is known that the significance value is less than 0.05 (0.00 <0.05), the conclusion is that the average results VO2Max from the three groups are significantly DIFFERENT. Based on the analysis above, it can be concluded that there is an increase in balance and VO2Max for each group, through ANOVA analysis. Where the aerobics exercise Low Impact has a better effect than the 2017 SKJ exercise and the control group, on balance and VO2Max.